Avelumab plus Axitinib versus Sunitinib for Advanced Renal-Cell Carcinoma - Motzer, Robert J; Penkov, Konstantin; Haanen, John; Rini, Brian; Albiges, Laurence; Campbell, Matthew T; Venugopal, Balaji; Kollmannsberger, Christian; Negrier, Sylvie; Uemura, Motohide; Lee, Jae L; Vasiliev, Aleksandr; et al. (The New England journal of medicine, 2019)
Among 886 patients with advanced renal-cell cancer, median progression-free survival was 13.8 months among those assigned to avelumab plus axitinib and 7.2 months among those assigned to sunitinib. Toxic effects of grade 3 or higher were similar in the two groups.